Realisasi Tindak Tutur Direktif Memohon Dalam Surat Izin Siswa Di Kabupaten Karanganyar - Farhan, Reno Ahmad; , Prof.Dr. Harun Joko Prayitno,M,Hum (2016)
The background of this issue to find out the meaning behind the speech in the permit students. Speech act is a speech activity that occurs in a particular situation said. The purpose of this study is twofold. (1) To identify and describe the directive speech acts pleaded in the permit students in Karanganyar. (2) To determine the application scale of modesty in speech acts directive begging in the permit in Karanganyar. This research was conducted at SMP Negeri 1 Gondangrejo and in SMA Gondangrejo. This study used a technique see, library, and note. This research was conducted by taking a students permit in school. The method used is a pragmatic match. This study indicates 33 sources of data taken note that 23 acts of politeness using rective pleading, 7 using the follow politeness directive asks, 3 using acts of politeness directive expect. The results of this study indicate the form directive speech acts pleaded in the permit students in Karanganyar there are 3 types of speech acts directive, (a) speech acts begging, (b) speech acts request (c) speech acts expect. The findings in this study there are three. (1) The use of directive speech acts begging. (2) The need Pn create a permit to Mt. (3) The similarities and differences between the results of the study authored by researchers with penetitian studied by other researchers.